PENGARUH LEADER MEMBER EXCHANGE DAN SELF EFFICACY KARYAWAN TERHADAP EMPLOYEE VOICE BEHAVIO DI PD. BPR ROKAN HULU - Anisah Hasibuan; Seprini (Program Studi Manajemen Universitas Pasir Pengaraian, 2020)
This study aims to see whether leader member exchange and self efficacy affect employee voice behavior in PD. BPR Rokan Hulu both partially and simultaneously. The population in this study were PD employees. BPR Rokan Hulu. The study sample used 34 census sampling techniques. The independent variables in this study were leader member exchange (X1), self efficacy (X2) and the dependent variable (Y) employee voice behavior. Data collection methods using observation, questionnaire and interview methods. Data analysis using multiple linear regression analysis using the SPSS program. The results of multiple linear regression analysis obtained regression equation Y = 5.478 + 0.246X1 + 0.270X2 Partially, obtained t-count leader member exchange is 3.096 and self efficacy is 5.696. Simultaneously, obtained an F-count of 34,100 shows leader member exchange and self efficacy jointly influencing employee voice behavior in PD. BPR Rokan Hulu. The results showed that 68.7% of employee voice behavior was influenced by leader member exchange and self efficacy, while the remaining 31.3% was influenced by other variables not examined in this study. The conclusion of this study both partially and simultaneously leader member exchange and self efficacy affect employee voice behavior in PD. BPR Rokan Hulu.